Illness Experiences of Adolescents with Type 1 Diabetes - Ji Eun Kim (Journal of Diabetes Research)
Objective. This study is aimed at exploring the illness experiences of adolescents with type 1 diabetes (T1D). Methods. Using semistructured questions, 12 adolescents with T1D in Korea were interviewed regarding their illness experiences. Data were analyzed using grounded theory methodology. Results. Participants described their experiences in the core category, “becoming myself again,” which resulted in 130 concepts, 36 subcategories, 13 categories, and five themes. The themes included tied, overwhelmed, running away, struggling, and conciliating. Tied, the first process, entailed three categories: “confined to blood sugar control,” “feeling constrained,” and “supervised by parents.” The overwhelmed process included “self-banished” and “surrounded by stigma.” Running away included three categories—“growing up,” “folding,” and “withdrawal.” Struggling entailed “seeking for solution to overcome,” “developing response skills,” and “accepting help.” The last process, conciliating, included “redefining my perspective” and “reconciling with myself.” Conclusions. The findings indicate that the illness experience of adolescents with T1D should be understood in terms of both physical and psychosocial dimensions, considering the sociocultural and developmental context. The results of this study provide valuable information on diabetes education. Moreover, these findings encourage nurses to develop intervention programs and strategies to help adolescents with T1D.